Self-defining memories of mothers of martyrs - Mohammed, Marwa Kazem (Edelweiss Applied Science and Technology, 2025)
The psychological well-being of bereaved women may be impacted by a range of problems, such as memories that define them. Grief lasting a long time can affect mothers who have experienced loss in all areas of their lives. They are subjected to a continuous cycle of intense longing and nostalgia that can lead to a strong preoccupation with the deceased. It is evident that their memories are devoted solely to the deceased, particularly the painful ones. Singer et al. were the ones who adopted the researcher's approach. The (2000-2001) scale was distributed across four areas, with a narrative dimension that can be answered by recalling three memories, and an emotional dimension that can be answered by seven alternatives. It was observed in the results that mothers who have been bereaved have low self-defining memories.